2022
DOI: 10.7759/cureus.21066
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Auditing Surgical Records in a Tertiary Hospital Setting

Abstract: Background: Assessing and improving quality of care should be of paramount importance to health care systems and providers. This study aimed to evaluate the quality of surgical records at the Jordan University Hospital.Methods: We used the previously validated Surgical Tool for Auditing Records (STAR) to retrospectively evaluate the quality of surgical records of patients who underwent surgery in the general surgery department from 2016 to 2021. Total STAR and section-specific STAR scores were compared using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The quality of surgical notes has significant economic and medicolegal effects in addition to its intrinsic medical implications. Additionally, properly documented records can be helpful for research advancement and auditing, which can enhance patient care delivery [ 21 ]. We have observed that the referral from where the patient came from was left out of the documentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of surgical notes has significant economic and medicolegal effects in addition to its intrinsic medical implications. Additionally, properly documented records can be helpful for research advancement and auditing, which can enhance patient care delivery [ 21 ]. We have observed that the referral from where the patient came from was left out of the documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Other methodologies like e-CRABEL and The Surgical Tool for Auditing Records (STAR) are modified versions of the CRABEL system that are more tailored to surgical records auditing and have been used in other studies with promising improvements [ 21 , 22 ]. Surgical Hospital Audit of Record Keeping (SHARK) is a new audit and teaching tool for junior doctors based on the Royal College of Surgeons guidelines to anonymously score the different surgical teams' medical records within a hospital [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In developed nations, there exists a highly effective national audit and comparative audit services system [ 11 ]. Alqudah et al [ 12 ] investigated the quality of surgical audits in a tertiary hospital in Jordan. This study showed that all elements of surgical audits had improved from baseline and that electronic materials and better personnel education could achieve higher performance in the surgical department.…”
Section: Discussionmentioning
confidence: 99%